Thailand Financial Sector Assessment Program : Implementation of the IOSCO Objectives and Principles of Securities Regulation - International Monetary Fund; World Bank (Washington, DC, 2017)
The responsibilities of the regulator should be clearly and objectively stated. The regulator should be operationally independent and accountable in the exercise of its functions and powers. The regulator should have adequate powers, proper resources and the capacity to perform its functions and exercise its powers. The regulator should adopt clear and consistent regulatory processes. The staff of the regulator should observe the highest professional standards including appropriate standards of confidentiality. The regulatory regime should make appropriate use of Self-Regulatory Organizations (SROs) that exercise some direct oversight responsibility for their respective areas of competence, and to the extent appropriate to the size and complexity of the markets. SROs should be subject to the oversight of the regulator and should observe standards of fairness and confidentiality when exercising powers and delegated responsibilities. The regulator should have comprehensive inspection, investigation and surveillance powers. The regulator should have comprehensive enforcement powers. The regulatory system should ensure an effective and credible use of inspection, investigation, surveillance and enforcement powers and implementation of an effective compliance program. The regulator should have authority to share both public and non-public information with domestic and foreign counterparts. Regulators should establish information sharing mechanisms that set out when and how they will share both public and non-public information with their domestic and foreign counterparts. The regulatory system should allow for assistance to be provided to foreign regulators who need to make inquiries in the discharge of their functions and exercise of their powers.